Geography-Based Budget Allocation for Digital Transformation of SMTK in Maluku 3T - Lulu bin Tahir Achmad (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2026)
This Policy Paper describes that digital transformation in religious secondary education is a strategic component of national education reform aimed at strengthening governance, accountability, and service quality. However, the implementation of digital transformation in Sekolah Menengah Teologi Kristen (SMTK) located in disadvantaged, frontier, and outermost (3T) areas of Maluku Province still faces structural constraints, particularly related to infrastructure availability and the design of budget allocation mechanisms. This study aims to analyze the problem of facilities and infrastructure budget allocation that has not yet been based on geographical needs and to examine its implications for the effectiveness of digital transformation. The study applies a qualitative policy analysis approach through document analysis using the perspectives of distributive justice, needs-based budgeting, and affirmative regional policy. The results indicate that the current allocation mechanism still relies on a uniform national formula and does not incorporate geographical weighting parameters or indicators of digital inequality. Consequently, resource distribution has not been fully responsive to the characteristics of 3T regions, resulting in limited institutional readiness and widening disparities in digital infrastructure support. This paper therefore recommends reformulating the budget allocation mechanism by integrating geographical weighting coefficients and digital infrastructure indicators into the funding formula to enhance proportionality in resource distribution and strengthen digital transformation in religious secondary education institutions in Maluku Province.